Tracking forest carbon and growth in large-scale passive restoration using multi-temporal airborne lidar - Felipe N. Begliomini; Fabian Jörg Fischer; Srinivasan Keshav; Pedro H.S. Brancalion; Paulo G. Molin; Angelica M. Almeyda Zambrano; Angélica Faria de Resende; Cassio Toledo; Catherine Torres de Almeida; Danilo Roberti Alves de Almeida; Davi Ernesto Alvarenga César; Eben N. Broadbent; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Fuel-Independent exhaust emission indices and equivalent limits up to Euro 7 with application to CFD combustion modelling - Francisca Guerrero-Villar; Eloísa Torres-Jiménez; Jordana Abdalla; Octavio Armas; Felipe Soto (Fuel, 2026)

Anatomopathological aspects of osteoarticular lesions associated with Rhodococcus equi infection in two foals - Felipe Martins Pastor; Suzyane Oliveira Barros; Letícia Fernandes Campos; Acácia Eduarda de Jesus Nascimento; Gabriel Henrique Guimarães; Carlos Renato de Souza Guimarães Filho; Luis Ernesto Campos Torres; Pâmela Aparecida de Lima; Andressa Batista da Silveira Xavier; Rodrigo Otávio Silveira Silva; Roberto Maurício Carvalho Guedes; Rogéria Serakides; et al. (Veterinary Research Communications, 2026)
Rhodococcus equi is an important bacterium that affects foals up to six months of age, especially those that are immunocompromised. The main manifestation is pyogranulomatous pneumonia; nevertheless, extrapulmonary lesions have not only been reported, but are not uncommon, including arthritis and osteomyelitis. Despite the widespread occurrence of rhodococcosis, the macro- and microscopic lesions in the musculoskeletal system are still poorly understood, and a detailed study is needed to better understand the pathogenic potential of the organism. The aim of this report is to present the anatomopathological aspects of bone and joint lesions associated with Rhodococcus equi in two foals. The first case was a two-month-old male Quarter Horse foal with suspected cervical trauma. This horse was admitted in lateral recumbency, semi-comatose, and with atlantoaxial region enlarged. Necropsy revealed atlantooccipital arthritis with pyogranulomatous osteomyelitis, resulting in pathologic fractures of the atlas. There was also pyogranulomatous pachymeningitis leading to compressive myelopathy. In the second case, a two-month-old Brazilian Sport Horse foal presented with lameness of the left pelvic limb and enlargement of the left femorotibial and femoropatellar and right scapulohumeral joints. Necropsy revealed femorotibial and femoropatellar arthritis and purulent osteomyelitis in the femur, as well as extensive necrosis and bone rarefaction with focal detachment of the epiphyseal plate. Both animals had pyogranulomatous pneumonia and lymphadenitis with extracellular and intracytoplasmic gram-positive coccobacilli in neutrophils and macrophages. In the first case, R. equi was isolated and confirmed by MALDI-TOF. R. equi infection should be considered in the differential diagnosis of osteoarticular lesions in foals.

Soil physical quality and organic carbon dynamics in low-input perennial rubber plantations across a chronosequence in the Brazilian Cerrado - Luís Felipe Leite Sabino de Oliveira; Lucas Eduardo de Oliveira; Taísa Cristina Tinoco; Fernando Antônio de Souza; Hamilton César de Oliveira Charlo; Leonardo Carneiro Morgado; Arcângelo Loss; Dinamar Márcia da Silva Vieira; José Luiz Rodrigues Torres (Agroforestry Systems, 2026)

Bamboo leaves as underexplored food sources: A systematized review of nutritional composition and analytical methodologies - Juliana A. Camponogara; Carla A.A. Farias; Grasielle D. Mathias; Andreara R. dos Reis; Stéphanie P. Torres; Isac G. de Oliveira; Felipe S. Molina; Cristiano A. Ballus; Milene T. Barcia (Food Bioscience, 2026)

Evaluation of biofuel and renewable ether blends for cleaner bioenergy transitions: Emissions mitigation and performance in compression ignition applications - Kleber Nunes Silva; Pedro Bancillon Ventin Muniz; Felipe Andrade Torres; Ednildo Andrade Torres (Biomass and Bioenergy, 2026)

Experimental gasification of glycerol-impregnated eucalyptus biomass for hydrogen-rich syngas - Daniela Araújo Costa; Marcos Fábio de Jesus; Felipe Lima de Araújo; Felipe Andrade Torres; Delano Mendes de Santana; Silvio A.B.V. de Melo; Francisco Jarmeson Silva Bandeira; Ednildo Andrade Torres (Biomass and Bioenergy, 2026)

Nutritional supplement based on spent substrate of the edible mushroom Pleurotus ostreatus for stable sheep - Jesús Antonio Pineda-Alegría; Lilia Moreno-Ruíz; René Humberto Andrade-Gallegos; Juan Felipe de Jesús Torres-Acosta; Alex Córdoba-Aguilar; Liliana Aguilar-Marcelino (Tropical Animal Health and Production, 2026)

Correction: Three-season evaluation of partial root zone drying as a water-saving strategy in commercial Chilean vineyards: effects on Carménère and Merlot - Daniel Knopp; Pilar M. Gil; Daniela Cea; Claudia Bonomelli; Natalia Brossard; Edmundo Bordeu; Alejandra Zúñiga; Héctor Ibarra; Felipe Torres; Camila Poblete; Diego Rodríguez (Irrigation Science, 2026)

Copper and lead trigger distinct responses in two Brazilian mosses - Mateus Fernandes Oliveira; Tiago Vilas-Boas; Felipe Della-Torre; Najla Meireles-Medeiros; Raphael Ricon de Oliveira; Marcel Giovanni Costa França; Lucas Anjos Souza; Adaíses Simone Maciel-Silva (Theoretical and Experimental Plant Physiology, 2026)
Metal contamination, particularly by copper (Cu) and lead (Pb), is a persistent environmental threat, yet the adaptive responses of Neotropical bryophytes to such stressors remain largely unexplored. This study evaluated biomass production, photosynthetic performance, and metal accumulation in two native Brazilian mosses ( Campylopus savannarum (Müll.Hal.) Mitt. and Polytrichum juniperinum Willd. ex Hedw.) exposed to increasing concentrations of Cu and Pb under controlled laboratory conditions. We hypothesized that their contrasting morpho-anatomical traits, especially differences in lamellae structure, photosynthetic surface organization, and the presence of conduction tissues, would lead to distinct physiological strategies of metal tolerance. At the end of 240 days, biomass and maximum quantum efficiency of PSII ( Fv/Fm ) were assessed, and tissue metal concentrations were quantified. The moss P. juniperinum exhibited remarkable tolerance, maintaining stable biomass and photosynthetic capacity across all treatments, while C. savannarum presented pronounced declines, especially under high Pb exposure. Both species displayed dose-dependent metal accumulation but with distinct patterns: C. savannarum accumulated nearly 196-fold more Cu at the highest treatment compared to the control, whereas P. juniperinum stored about 44-fold more Pb than the control. These contrasting responses likely reflect species-specific strategies of metal tolerance. These results position Neotropical mosses as valuable bioindicators and potential agents for generating genomic data to improve our understanding of metal tolerance in bryophytes. Future research should investigate tissue-concentration metal partitioning and the molecular mechanisms underlying tolerance in native Brazilian bryophytes.

Optimisation of a novel monolith multicapillary bioreactor for methane bioconversion into value-added products - Bruna Sampaio de Mello; Nerea Rodriguez Pardo; Patricia Zamora; Víctor Monsalvo; Frank Rogalla; Andrés Felipe Torres-Franco; Raúl Muñoz Torre (Process Safety and Environmental Protection, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Adoption of silvopastoral systems: a comprehensive systematic review and bibliometric analysis of global perspectives and trends - Lucas Abreu Kerkoff; Carlos Moreira Miquelino Eleto Torres; Dietrich Darr; Aldicir Osni Scariot; Eraldo Aparecido Trondoli Matricardi; Felipe Corrêa Ribeiro; Kathrin Meinhold; Silvio Nolasco de Oliveira Neto (Agroforestry Systems, 2026)
Beef and dairy production from cattle farming operate under two main systems: feedlot and pasture based systems, both of which are potentially associated with deforestation due to feed-crop cultivation and pasture expansion. Poor pasture management and ongoing land conversion further exacerbate environmental degradation, posing a significant global conservation challenge. Agricultural innovations such as silvopastoral systems (SPS) emerge as a sustainable alternative to mitigate the negative effects of conventional livestock farming. Despite documented benefits, the adoption of these systems remains low. This study presents a combined bibliometric analysis and systematic review of international research on the adoption of SPS. The review utilized the Scopus database and employed the PRISMA methodology, resulting in a total of 58 documents selected and analyzed. The study identified the main countries in terms of publications on SPS adoption as: the United States, Germany, Colombia, Brazil, and Mexico, whereas the location of most SPS studies were from Colombia and USA, Brazil and Mexico, and Panama. The results show that less complex systems such as SPS with scattered trees, riparian buffers, and live fences present the highest average adoption rates (> 50%) due to lower management intensity. Adoption rates varied by region, with higher uptake in tropical climates where ecological conditions and policy incentives support implementation. Key factors influencing adoption included payment for environmental services, government subsidies, and labor demands, with high costs and limited knowledge acting as barriers. Understanding region-specific drivers is essential, highlighting the need for further research to address existing gaps in a local level.

Enhancing Raphanus sativus seed germination through ultrasound pretreatment and an automated system - Daniel Aguilar-Torres; Omar Jiménez-Ramírez; Guillermo Luque-Zuñiga; Felipe A. Perdomo; Rubén Vázquez-Medina (Next Research, 2026)

Fluvial dynamics of the Grande River and paleolandscape evolution in Northeastern Brazil - Mateus Moriconi Prebianca; Vinícius Borges Moreira; Bruno Araújo Torres; André de Oliveira Souza; Everton Vinicius Valezio; Felipe Gomes Rubira; David Oldack Barcelos Ferreira Machado; Luca Lämmle; Archimedes Perez Filho (Geomorphology, 2026)

Boosting the energy transition in the transport sector through the use of sustainable alcohol–diesel blends - Pedro Ventin; Juan José Hernández; Felipe A. Torres; Ednildo A. Torres; Magín Lapuerta (Biomass and Bioenergy, 2026)

Evaluating a novel helical screw torrefaction reactor: A PrOPPAGA-based benchmarking of continuous biomass torrefaction technologies - Marcos Fábio de Jesus; Daniela Araújo Costa; Francisco Jarmeson Silva Bandeira; Felipe Andrade Torres; Delano Mendes de Santana; Ednildo Andrade Torres; Sílvio A.B.V. de Melo (Biomass and Bioenergy, 2026)

Into new depths: climate-driven habitat expansion of the endangered skate Dipturus chilensis (Chondrichthyes, Rajiformes) - Jaime A. Villafaña; Diego Almendras; Daniel González-Aragón; Felipe I. Torres; Francisco J. Concha; Ana B. Guzmán-Castellanos; Ignacio Contreras; Karina E. Buldrini; Pablo Oyanadel-Urbina; Carolina A. Sandoval; Benjamín Miranda; Gabriel Mazo; et al. (Marine Environmental Research, 2026)

Viral RNA and antibiotic resistance genes associations in a full-scale activated sludge wastewater treatment plant - Andrés Felipe Torres-Franco; Elisa Rodríguez; José Gonçalves; María José González; Raúl Muñoz; Pedro A. García-Encina; Israel Diaz (Journal of Environmental Chemical Engineering, 2026)

Oil spill analysis and simulations in the Foz do Amazonas sedimentary basin - Felipe R. Torres; Syumara Queiroz; Carlos A.D. Lentini; L.F.F. Mendonça; André T. Cunha Lima (Continental Shelf Research, 2026)

Systematics of Chironius laurenti Dixon, Wiest and Cei 1993 (Serpentes: Colubridae) reveals unexpected taxonomic insights - Vinícius Sudré; Luis M. P. Ceríaco; Omar Torres-Carvajal; Christine Strüssmann; Felipe Franco Curcio; Guarino R. Colli; Paulo Passos (Organisms Diversity & Evolution, 2026)
Chironius laurenti was described based on 27 specimens from localities of the Beni savanna and Chiquitano Dry Forest in Bolivia and one specimen from the Brazilian Cerrado. We examined the holotype of C. laurenti from the department of Beni, Bolivia, as well as most of the paratypes and expanded sample obtained in zoological collections. Based on morphological and molecular data, we restrict the name C. laurenti to the populations distributed throughout the Madeira River Basin and conclude that the known records throughout the Pantanal wetlands and transition areas with the Cerrado savanna represent a distinct entity erroneously attributed to this name. Therefore, we describe the latter populations as a new species endemic to the Upper Paraguay River Basin, distinguished from its congeners by a unique combination of qualitative and quantitative morphological characters (meristic, color pattern, and cranial osteology) and unequivocal molecular evidence. We report on relevant behavioral observations of the new species, specifically its foraging strategy on riverbanks and male-male combat, which may occur during the mating season. Additionally, we discuss possible diversification hypotheses in the Upper Paraguay River Basin and highlight the importance of conserving ecological corridors linking the Pantanal to the surrounding plateaus, as ongoing climate changes may restrict or displace present species’ distributions. http://www.zoobank.org/urn:lsid:zoobank.org:pub:D1DCEB24-8C69-4B76-8387-CD9ACB23C733 .

Recycling waste, recycling risk: cypermethrin-contaminated poultry litter triggers sublethal toxicity in Folsomia candida at realistic environmental concentrations - Monizze Vannuci-Silva; Carolina C.S. Gomes; Lucas V. Sousa-Lima; Sidney F. Sales Junior; Evelyn O. Silva; Mariana F. Maia; Felipe Lucena; João Paulo M. Torres; Olaf Malm; Júlia C. Niemeyer; Enrico M. Saggioro; Cláudio E.T. Parente (Chemosphere, 2026)

Spatial heterogeneity in mussel larval abundance across fjord systems of northern Chilean Patagonia - Felipe I. Torres; Carlos Lara; Carlos Molinet; Nicole Castillo-Villagrán; Bernardo R. Broitman (Journal of Marine Systems, 2026)

Physiological and Proteomic Shifts in Pfaffia glomerata Under Drought and Elevated CO₂ - Tatiane Dulcineia Silva; Evandro Alexandre Fortini; Diego Silva Batista; Kerly Jessenia Moncaleano Robledo; Mariana Machado; Sérgio Heitor Sousa Felipe; Tadeu dos Reis de Oliveira; Moab Torres de Andrade; Letícia Monteiro Farias; Claudete Santa-Catarina; Vanildo Silveira; Philipp Westhoff; et al. (Journal of Plant Growth Regulation, 2026)
Drought is a major constraint to plant growth and productivity, and rising atmospheric CO₂ concentrations are expected to modify plant responses to water limitation. However, how CO₂ enrichment reshapes the physiological, metabolic, and molecular regulation of specialized metabolite production under drought remains poorly understood. Here, we investigated the combined effects of elevated CO₂ (e[CO₂]) and drought on plant morphophysiology and on the production of 20-hydroxyecdysone (20E), a phytoecdysteroid of therapeutic relevance whose accumulation may be influenced by environmental stress, in Pfaffia glomerata . Plants were grown under ambient (± 400 µmol mol⁻ 1 ; a[CO₂]) or elevated (± 800 µmol mol⁻ 1 ; e[CO₂]) CO₂ concentrations combined with sufficient or limited water supply. Elevated CO₂ promoted a metabolic shift under drought, characterized by increased investment in osmoregulatory compounds, including soluble sugars, myo-inositol, and glutamate. In contrast, drought reduced photosynthetic pigments and several primary metabolites regardless of CO₂ level. Drought induced the expression of lignin biosynthesis genes ( PgC4H , PgCCoAOMT , and PgCAD ) under both CO₂ conditions; however, PgCCR was specifically upregulated under e[CO₂] combined with drought, with consistently higher transcript levels than under ambient CO₂. Proteomic analyses revealed that e[CO₂] attenuated the accumulation of many canonical drought-responsive proteins, while selectively promoting the accumulation of the cytochrome P450 CYP72A219-like protein, which was associated with increased whole-plant 20E production. Together, these findings show that drought drives 20E biosynthesis, while elevated CO₂ modulates drought response intensity and allocation, ultimately affecting total 20E yield per plant and its relevance under future climate scenarios.

Three-season evaluation of partial root zone drying as a water-saving strategy in commercial Chilean vineyards: effects on Carménère and Merlot - Daniel Knopp; Pilar M. Gil; Daniela Cea; Claudia Bonomelli; Natalia Brossard; Edmundo Bordeu; Alejandra Zúñiga; Héctor Ibarra; Felipe Torres; Camila Poblete; Diego Rodríguez (Irrigation Science, 2026)

Key factors of the deranged antiviral response in elderly patients with COVID-19: a machine-learning analysis - Tamara Postigo-Casado; Alicia Ortega; Alejandro Álvaro-Meca; Daniel Vélez-Serrano; Nadia García-Mateo; Ana P. Tedim; Raquel Almansa; Jose María Eiros; David de Gonzalo-Calvo; Anna Moncusí-Moix; Clara Gort-Paniello; Manel Perez-Pons; et al. (GeroScience, 2026)
Age is a well-known risk factor to develop severe viral respiratory infections, including severe COVID-19. This study aimed to identify the biological alterations linked to severe disease in elderly patients with COVID-19. For this purpose, we employed a derivation cohort with 450 SARS-CoV-2 infected and unvaccinated patients admitted to hospital wards and a validation cohort with 244 SARS-CoV-2 infected and unvaccinated patients admitted to hospital Intensive Care Unit (ICU). Twenty-one biomarkers were measured in plasma samples from patients upon admission, including SARS-CoV-2 RNA, IgG antibodies, and protein biomarkers. Patient cohorts were divided into two groups based on age: adult (≤ 70 years old) and elderly (> 70 years old) patients. In the derivation cohort, 90-day mortality rate observed in the adult group was 6.0% whereas in the elderly group it rises to 31.6%, same trend was noticed regarding the validation cohort, with 11.2% versus 40.3% 90-day mortality rates for adult and elderly groups, respectively. The machine-learning framework XGBoost-SHAP, fed with the plasma biomarkers information, was used to profile an age-related host response to SARS-CoV-2 infection. Based on SHAP plot, elderly patients had a strong thrombo-inflammatory response profile (significantly elevated plasma levels of: lipocalin-2, endothelin-1, D-dimer) combined with deficient adaptive and cytotoxic antiviral responses. Model performance evaluated with the validation cohort confirmed the robustness and generalizability of the model developed (AUC = 0.710). In conclusion, the machine learning approach we built allowed us to identify the presence of a deranged host response in elderly patients with COVID-19 linked to poor viral control and increased mortality. Graphical Abstract

The in vitro exsheathment kinetics of Trichostrongylus colubriformis L3 in ruminal, abomasal, and two-stage incubation protocols - Dilcia Yobed Miranda-Miranda; Cindy Goretti Marin-Tun; Concepción Manuela Capetillo-Leal; María Gabriela Mancilla-Montelongo; Carlos Alfredo Sandoval-Castro; Juan Felipe de Jesús Torres-Acosta (Veterinary Parasitology, 2026)

Sex assessment in a hominin upper second molar (RV’23-350) from the Ruidera (Spain) Middle Pleistocene paleoanthropological site: a proteome-based analysis of the amelogenin - Daniel García-Martínez; Paula Sanz-Henche; Inés Zapico; Luis Felipe Clemente; Maria Luisa Hernáez; Luis Ríos; Mar Casquero; Candelas Buenestado Ruíz; Darío Fidalgo; Sara Díaz-Pérez; Isidoro Campaña Lozano; Lucía Bermejo; et al. (Quaternary International, 2026)

Impact of in vitro static digestion of geopropolis and propolis extracts from stingless bees on antioxidant activity and total content of bioactive compounds - Maidelen Del Carmen Lozano Guerrero; Ana Beatriz Hortmann; Luiz Felipe Bodnar; Gislaine Pucholobek; Sueli Pércio Quináia; Alex Fragoso Sierra; Yohandra Reyes Torres (Food Research International, 2026)

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

Genetic additive components of the exoskeleton mineral profile and their genetic relationship with growth traits in Penaeus vannamei - Marina Martínez Soler; Hyun Suk Shin; Álvaro Lorenzo-Felipe; María Jesús Zamorano Serrano; Rafael Ginés Ruiz; Laura Pachón Mesa; Octavio Luis Pérez Luzardo; Manuel Zumbado Peña; Norberto Ruiz Suárez; Ángel Rodríguez Hernández; Jesús Fernández Martín; Ricardo Torres; et al. (Frontiers in Marine Science, 2026)
Introduction The aquaculture industry faces challenges due to the limited availability and environmental impact of fishmeal. As alternative diets are adopted, mineral supplementation through feed, water, or substrate has become essential to sustain shrimp performance. A promising but unexplored approach is genetic selection to enhance mineral content, offering a sustainable complement to supplementation strategies. This work represents the first study of genetic parameters for mineral content in the most widely produced aquaculture species, the white leg shrimp. Methods To this aim, 388 shrimp from 79 full-sib and 18 half-sib families of the PMG-BIOGEMAR© breeding program selected focused on growth by harvest weight under low salinity industrial conditions in Ecuador were analyzed. Animals were sampled at harvest size and transferred to the University of Las Palmas de Gran Canaria to measure weight and length, and mineral concentrations of their exoskeletons by inductively coupled plasma mass spectrometry. Genetic parameters for these traits were obtained by Bayesian estimation method. Results and Discussion Genetic parameters for these traits were obtained by Bayesian estimation method. Interestingly, the concentration of Cu, Na, K, Mg, Ca, and P presented medium heritability (from 0.20 to 0.42), the highest being Cu. While Fe, Mn, and Zn showed low heritability (from 0.07 to 0.18), the lowest being Fe. Overall, the genetic correlations estimated among minerals suggest that their levels can be improved simultaneously through genetic selection, offering a viable strategy to face the future challenges of shrimp production in low-salinity environments. However, the lengthy time and high costs of the mineral analysis could prompt the consideration of modulating mineral content through indirect selection based on a growth trait with high genetic correlations (positives or negatives) with mineral content. Thus, positive indirect selection can be applied to increase Ca and Mg levels, while negative indirect selection for Fe, Zn, and Cu may help maintain balanced concentrations and mitigate the effects of anthropogenic inputs.

Hydrogeological suitability of Coahuila, Northeast Mexico: An integrated bibliometric, GIS, and water quality assessment - Ramón Yosvanis Batista Cruz; Yuri Almaguer Carmenates; José Alberto Batista Rodríguez; Felipe de Jesús López Saucedo; Yalina Montecelos Zamora; Brenda Margarita Salas Ramos; Aylin Karel Ibarra Torres; Frida García Robles; Luis Eutiquio Canales Gutiérrez (Journal of South American Earth Sciences, 2026)

Screening of antiviral activity in freshwater and marine microalgae: Inactivation capacity over enveloped and non-enveloped viruses - Antonio Leon-Vaz; Lucía Tejero-Álvarez; Pedro Antonio García-Encina; Raúl Muñoz; Andrés Felipe Torres-Franco (Journal of Environmental Management, 2026)

Influence of biomilking on methanotrophs cultivation during biogas conversion into ectoines - Andrés Felipe Torres-Franco; Raquel Herrero-Lobo; Raquel Lebrero; Raúl Muñoz (Bioresource Technology, 2026)

Triacylglycerol accumulation in Rhodococcus opacus DSM 43205 from Knallgas and Knallgas-derived soluble intermediates - Blanca Araya; Paz Torres-Praderio; Raúl Conejeros; Alberto Vergara-Fernández; Felipe Scott (Journal of Environmental Chemical Engineering, 2026)

Climatic forcing modulates non-stationary environmental synchrony in shellfish production regions - Carlos Lara; Richard Muñoz; Sebastián I. Vásquez; Felipe I. Torres; Amalia M.S. Detoni; Bernardo R. Broitman; Bernard Cazelles (Estuarine, Coastal and Shelf Science, 2026)

Systematic review of the prevalence of Gastrointestinal helminths in ruminants in Mexico - Roberto González-Garduño; Rosa Isabel Higuera-Piedrahita; Jorge Alfredo Cuéllar-Ordaz; Abel Villa-Mancera; Pedro Mendoza-de Gives; J. Felipe Torres-Acosta (Veterinary Research Communications, 2026)
In Mexico, the abundance of endoparasites that affect the health of ruminants and the economy of the farmer, so the objective of this review was to determine the prevalence of the main genera and species of ruminant helminths that have been identified in Mexico in the last 37 years. A systematic search was carried out following the PRISMA 2020 guidelines and supported by the Elsevier platform (Scopus and ScienceDirect), Google Scholar, Redalyc and Scielo tools. In addition, information was sought in the proceedings Congress of the Buiatrics and Veterinary Parasitologists. A database was created with 36 documents containing information on the prevalence of gastrointestinal parasites in Mexico. Research studies that included treatments that affected prevalence were not included, nor were those of an experimental nature that did not aim to study prevalence. The prevalence for Haemonchus contortus , the main abomasal nematode in ruminants, was 38.8%. In the case of Mecistocirrus , only four studies indicated the prevalence in cattle, which was estimated at 40.5%. In the small intestine, the most prevalent nematode in cattle were Cooperia and Strongyloides . In goats and sheep, the presence of Trichostrongylus , and Toxocara were indicated. The main cecal nematodes include Trichuris and in the colon Oesophagostomum and Chabertia . The high prevalence of gastrointestinal nematodes in ruminants makes it essential to consider control measures to reduce their prevalence.

Assessment of Vancomycin Penetration into Cerebrospinal Fluid in Patients with Ventriculitis Using a Physiologically Based Pharmacokinetic Approach - Larissa Martins Alves Guimarães; Letícia Oliveira de Vasconcellos Nacif; Jhohann Richard de Lima Benzi; Mayra Torres de Oliveira Santos; Carolina Yamada; Felipe Francisco Tuon; João Paulo Telles; Fernanda de Lima Moreira (Pharmaceutical Research, 2026)
Introduction Vancomycin is an antimicrobial agent for treating central nervous system (CNS) infections caused by Gram-positive bacteria. Due to practical and ethical reasons, it is difficult to evaluate vancomycin exposure in cerebrospinal fluid (CSF) and its relationship with therapeutic outcomes. Therefore, alternative methodologies are required. We developed a physiologically based pharmacokinetic (PBPK) model to characterize vancomycin exposure in plasma and CSF in patients with ventriculitis enrolled in a therapeutic drug monitoring program. Methodology PBPK modeling and simulation were conducted using PK-Sim® version 11.3. A PBPK model was constructed to simulate vancomycin exposure in plasma and CSF. Physicochemical parameters of vancomycin were incorporated into a large molecule model, and tissue distribution was described using the Rodgers-Rowland model. Results The final PBPK model incorporated vancomycin’s low brain permeability by adjusting the CSF-to-plasma partition coefficient to 0.17. Model validation was performed using data from 33 patients with ventriculitis under external ventricular drainage. The dosing regimen consisted of a 30 mg/kg loading dose followed by a continuous intravenous infusion of 60 mg/kg/day. Mean simulated vancomycin concentrations in plasma and CSF were 32 mg/L and 7.2 mg/L, respectively. The predicted CSF/plasma concentration ratio was 0.22, which closely matched the observed ratio of 0.17. Conclusion Vancomycin penetration into the CNS is low and variable, highlighting the importance of therapeutic drug monitoring and individualized therapy in patients with ventriculitis. In the future, this model may facilitate the selection of optimal dosing regimens by simulating alternative dosing strategies and establishing PK/PD relationships for CNS infections.

Projections of Atmospheric Moisture Transport Over South America in a Changing Climate - Alvaro Avila‐Diaz; Roger Rodrigues Torres; Benjamin Quesada; Laís Rosa Oliveira; Alejandro Uribe; Paola A. Arias; Murilo Ruv Lemes; Cristian Felipe Zuluaga; Wilmar L. Ceron (International Journal of Climatology, 2026)
Climate change has intensified the global water cycle, increased atmospheric moisture, and altered precipitation patterns, leading to extreme rainfall events and droughts. South America is particularly vulnerable to these changes due to its complex climate dynamics and heavy reliance on agriculture and hydropower. This study investigates future projections of atmospheric moisture transport over South America, focusing on Vertically Integrated Moisture Flux (VIMF) and its convergence (VIMFC). Using high‐resolution ERA5 reanalysis data and 17 CMIP6 Earth System Models (ESMs), we analyse moisture transport patterns for 2071–2100 under four Shared Socioeconomic Pathways (SSP1‐2.6, SSP2‐4.5, SSP3‐7.0 and SSP5‐8.5), compared to a baseline period (1985–2014). The study evaluates 27 hydrological basins, revealing significant regional variations. Under SSP5‐8.5, northern Chile and eastern Brazil show increased moisture divergence, while basins like La Plata and Magdalena exhibit stronger convergence. The Peru Pacific Coast basin records the highest annual convergence (4.98 mm day −1 ), followed by Magdalena (2.25 mm day −1 ). Conversely, the North Chile Pacific Coast and the East Brazil's South Atlantic Coast showed the largest divergences (−4.54 and −2.99 mm day −1 , respectively). The research provides a novel basin‐level analysis of atmospheric moisture dynamics, linking changes in moisture transport and convergence directly to potential shifts in precipitation regimes. These results offer critical insights for water resource management, agriculture, and energy planning across South America. High model agreement across scenarios enhances the reliability of these projections, making the study a valuable resource for developing climate adaptation strategies, particularly in possible high‐impact regions like northern Argentina, the La Plata Basin, and eastern Brazil.

Distribution and morphology of the ampullae of Lorenzini in coastal and pelagic sharks from the Mexican Pacific - José Miguel Rangel-Morales; Rosa Isabel Ochoa-Báez; Julián René Torres-Villegas; Felipe Galván-Magaña (Regional Studies in Marine Science, 2025)

Phylogenetic and Functional Biogeographic Approach for Rodent Conservation Across an Environmental Gradient in Chile - Wendy C. Hernández‐Mazariegos; Felipe I. Torres; Reilly Brennan; Luis E. Escobar; R. Eduardo Palma; Christian M. Ibáñez (Journal of Biogeography, 2025)
Aim Understanding how abiotic factors influence species diversity, evolution and functional patterns of species is crucial for biodiversity conservation and for the management of terrestrial protected areas. We evaluate biogeographic and phylogenetic metrics in rodents to understand biodiversity patterns and improve wildlife conservation strategies. Location Chile, South America. Taxon Rodents (Mammalia, Rodentia). Methods We updated the phylogeny of rodent species in Chile using gene sequences retrieved from GenBank. We used the phylogenetic tree to calculate different biodiversity indices. We analysed Species Richness (SR), observed and standard effect size (SES) of Phylogenetic Diversity (PD), Phylogenetic Endemism (PE), and Functional Diversity (FD) across different ecoregions, climatic regions, and terrestrial protected areas along gradients of temperature and precipitation. Results We found high rodent diversity in north and central‐south Chile, and an association between phylogenetic and functional indices. Diversity indices (SR, SES.PD, SES.PE, SES.PE) were strongly associated with ecoregions, with the highest indices occurring in a high‐altitude ecoregion (i.e., Puna), Polar climatic region, and unprotected areas. Main Conclusions Spatial congruence among diversity indices suggests that species composition and evolutionary history play a fundamental role in structuring rodent species assemblages. Areas with high diversity indices delineate regions with high species richness that experience higher species diversification (PD), leading to ecological specialisation (FD) and endemism (PE). The linkages between diversity indices and ecoregions suggest that environmental heterogeneity within ecoregions drives variation in community composition. Environmental variation may be more pronounced in harsh habitats (e.g., Atacama Desert), while weak in benign habitats (e.g., Puna). The spatial mismatch between biodiversity hotspots and protected areas suggests that key evolutionary and ecological processes could be occurring outside current protected areas, raising concerns about the effectiveness of biodiversity conservation strategies.

Early response of soil bacterial communities to soil burn severity in pine and shrub vegetation after wildfire in temperate-humid climate - Juan A. Rubiolo; Felipe García-Oliva; José A. Vega; Yunuen Tapia-Torres; José M. Fernández-Alonso; Paulino Martínez; M. Teresa Fontúrbel (Science of The Total Environment, 2025)

Cellular toxicity of organotellurans: a systematic review of pre-clinical studies - Maria Luisa Lima Barreto do Nascimento; Isabela Ribeiro de Sá Guimarães Nolêto; Francisco Leonardo Torres-Leal; Felipe Cavalcanti Carneiro da Silva; João Marcelo de Castro e Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Gibberellin Regulates Sugar Metabolism and Modifies Cell Wall Composition in Soybean (Glycine max L. Merrill) - Raysa M. J. Sousa; Juliane M. Henschel; Diego S. Batista; Tatiane D. Silva; Sérgio H. S. Felipe; Gabriela Torres-Silva; Paulo V. L. Souza; Silvio A. Cândido-Sobrinho; Kristhiano Chagas; Kamila M. Castro; Evandro A. Fortini; Ludmila N. F. Correia; et al. (Journal of Plant Growth Regulation, 2025)

Characterization of perchlorate desorption and regeneration of the highly selective ion-exchange resin A530E using 1-butyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole hydroxide, and choline chloride - Diana Muñoz-Arango; Diego F. Montaño; Nicolas Veloso-Cid; Felipe Torres-Rojas; Roberto I. Canales; Mauricio Isaacs; Samuel A. Hevia; Ignacio T. Vargas (Journal of Environmental Chemical Engineering, 2025)

Antinociceptive, anti-inflammatory, and antiophidic potential of Punica granatum leaves extract and fraction: an in vitro and in vivo evaluation - Janaina Carla Barbosa Machado; Joyce Cristina da Silva; Wêndeo Kennedy Costa; Márcia Vanusa da Silva; Alisson Macário de Oliveria; Alessandra Daniele-Silva; Adriana Marina e Silva Parente; Sarah de Sousa Ferreira; Diana Pontes da Silva; Manoela Torres-Rêgo; Felipe França Cavalcanti; Matheus de Freitas Fernandes-Pedrosa; et al. (Inflammopharmacology, 2025)

Joubert syndrome with the decaying molar tooth sign: report of 2 cases - Felipe Scortegagna; Diogo Goulart Corrêa; Felipe Torres Pacheco; Renato Hoffmann Nunes; Antônio José da Rocha (Acta Neurologica Belgica, 2025)

Leptospirosis in marine mammals: An in-depth look at an underexplored ecosystem - Felipe D'A. Torres; Margaret E. Martinez; Michelle Rivard; Padraig Duignan; Katherine C. Prager; James O. Lloyd-Smith; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Research in Veterinary Science, 2025)

Reducing carbon footprint in high H2S emissions: A synergistic microalgal-bacterial solution for sugarcane biorefineries - André do Vale Borges; Andrés Felipe Torres Franco; Márcia Helena Rissato Zamariolli Damianovic; Raúl Muñoz Torre (Journal of Hazardous Materials, 2025)

Polyphenol metabolism, short-chain fatty acids production, and microbiota changes during in vitro digestion and fermentation of Chilean beans (Phaseolus vulgaris L.) - Nélida Nina; Carlo Bressa; Beatriz de Lucas; Isabel Martin de la Torre; Felipe Jiménez-Aspee; Guillermo Schmeda-Hirschmann; Mar Larrosa (Food Chemistry, 2025)

Microencapsulation of maillard reaction products from chicken bone protein hydrolysates: Retention and preservation of meat flavoring compounds - Rebeka Correia de Souza Cunha; Viviane Maria de Sousa Fontes; Eike Guilherme Torres de Souza; Gezaildo Santos Silva; Layane Rosa da Silva; Mercia de Sousa Galvão; Izabela Dutra Alvim; Angela Matilde da Silva Alves; Maria Teresa Bertoldo Pacheco; Felipe Lopes Brum; Sandro Marden Torres; Marta Suely Madruga; et al. (Food Chemistry, 2025)

Do feeding habits influence anthropogenic particle consumption in demersal fish in a tropical estuary? A study from the northern part of the Tropical Eastern Pacific - Carlos René Green-Ruíz; Felipe Amezcua; Roberto Cruz-García; José R. Rivera-Hernández; Víctor M. Muro-Torres (Frontiers in Marine Science, 2025)
Introduction The presence of anthropogenic particles (AP), defined as materials that have undergone human modification, in an estuarine system, and their consumption by demersal fishes, were assessed in the northern part of the Tropical Eastern Pacific. The aim was to investigate how the type and quantity of microplastics ingested by demersal fish of different trophic levels, feeding habits, and feeding guilds vary, and if these relate to the APs found in water. Methods Water and fish samples were collected from a network of stations through the estuarine system of Huizache-Caimanero. The presence and characteristics of microplastics were analyzed using Fourier Transform Infrared (FTIR) spectroscopy. A total of 1,162 AP particles were identified in the water samples, with fragments being the most common form. Stomach contents from 133 fish, representing six species across different trophic levels and feeding habits, were examined. These species included planktivores, carnivores, and omnivores, as well as zoobenthivores, piscivores, planktivores, and detritivores. Results The study found a high frequency of microplastic ingestion among fish, with fibers being the most prevalent form. The most common polymers identified in both water and fish were cotton and polyethylene terephthalate (PET). Other polymers detected included alkyd resins in water and nylon in fish, while polyethylene and acrylic were less abundant. These findings align with the types of human activities conducted in the study area. Discussion Our findings suggest that the position in the water column influences microplastic ingestion, rather than trophic position or feeding habits. This study provides valuable insights into the impact of AP contamination on coastal ecosystems and highlights the need for effective management strategies to mitigate its effects. Future research should focus on the long-term ecological impacts of microplastics and the development of sustainable solutions to address this growing environmental challenge.

Human impact on the functional diversity of Gerromorpha (Hemiptera: Heteroptera) and differential sexual dimorphism responses in Amazonian aquatic ecosystems - Alana Patricia Meguy Guterres; Erlane José Cunha; Felipe Ferraz Figueiredo Moreira; Naiara Raiol Torres; Leandro Juen (Science of The Total Environment, 2025)

Root-Stem Transition Zone Anatomy Assessment in Hormonal Variants of Tomato, After Growing Under Contrasting Water Saturation - Rodrigo Barbosa Kloss; Felipe Della Torre; Vinícius Politi Duarte; Fabricio José Pereira; Joni Esrom Lima; Marcel Giovanni Costa França (Journal of Plant Growth Regulation, 2025)

Tick fever agents in dairy cattle from a tropical region subjected to different breeding systems: Parasitological, clinical, serological aspects and genetic diversity of Anaplasma marginale - Alliny Souza de Assis Cavalcante; Nathalia Braz Ribeiro; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Rosangela Zacarias Machado; Marcos Rogério André; Ana Claudia Calchi; Felipe da Silva Krawczak; Lorena Lopes Ferreira; Camila Valgas Bastos; Filipe Dantas-Torres; Vando Edésio Soares; et al. (Research in Veterinary Science, 2025)

Enrichment of electrochemically active microorganisms in a chlorate-pressured environment - Angela Cantillo-González; Felipe Torres-Rojas; Rodrigo De la Iglesia; Ignacio T. Vargas (Journal of Environmental Chemical Engineering, 2025)

Impact of the alcohol chemical structure on pollutant emissions of a diesel engine under real driving conditions - Pedro Ventin; Magín Lapuerta; Felipe A. Torres; Ednildo A. Torres; Juan José Hernández (Fuel, 2025)

Multiphysics analysis for ultrasound settings that can disinfect food: Inactivation of E. coli in apples - Daniel Aguilar-Torres; Omar Jiménez-Ramírez; Regina Hernández-Gama; Felipe A. Perdomo-Hurtado; Rubén Vázquez-Medina (Food Control, 2025)

Aluminum accumulation in mosses from the Brazilian savanna: a comparative study of two species revealing similar traits to vascular plants - Mateus Fernandes Oliveira; Ígor Abba Arriola; Guilherme Henrique Rodrigues-Mattos; Felipe Della Torre; Joni Esrom Lima; Marcel Giovanni Costa França; Rosy Mary dos Santos Isaias; Adaíses Simone Maciel-Silva (Planta, 2025)

Association of TLR8 Variants in Sex-Based Clinical Differences in Patients with COVID-19 - María del Carmen Camacho-Rea; Laura Edith Martínez-Gómez; Carlos Martinez-Armenta; Gabriela Angélica Martínez-Nava; Silvestre Ortega-Peña; Jessel Olea-Torres; Brígida Herrera-López; Carlos Suarez-Ahedo; Paola Vázquez-Cárdenas; Rosa P. Vidal-Vázquez; Juan Pablo Ramírez-Hinojosa; Gilberto Vargas-Alarcón; et al. (Biochemical Genetics, 2025)

Climate-induced habitat shifts of farmed mussel species - Felipe I. Torres; Carlos Lara; Neftalí Sillero; Bernardo R. Broitman (Aquaculture, 2025)

Developing a microalgal-bacterial consortium for the removal of organic pollutants from petrochemical industry - Antonio León-Vaz; Andrés Felipe Torres-Franco; Pedro Antonio García-Encina; Raúl Muñoz (Journal of Water Process Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Reports on Work‐Related Injury and Diseases in Brazilian Aquaculture from Industry Participants - Gabriela Lenz; Cíntia Torres; Felipe de Assis Ribeiro; Alexsandro Vargas de Ávila; Kelly Cristina Tagliari de Brito; Benito Guimarães de Brito; Andréa Ferretto da Rocha; Lissandra Souto Cavalli (Journal of Agromedicine, 2025)

Oculomotor nerve trauma: the intensity matters in imaging interpretation - Diogo Goulart Corrêa; Ademar Lucas Júnior; Felipe Torres Pacheco (Acta Neurologica Belgica, 2025)

Cryopreservation and photomixotrophic cultivation of Pfaffia glomerata (Spreng.) pedersen genotypes enable the conservation of a valuable medicinal resource - Duanny Thais Rodrigues Caproni; Gabriela Torres-Silva; Diego Silva Batista; Ana Cláudia Ferreira Cruz; Sérgio Heitor Sousa Felipe; Kristhiano Chagas; Marcos Vinícius Marques Pinheiro; Wagner Campos Otoni (Vegetos, 2025)

Unraveling Ordovician-Silurian sedimentation: Facies, paleocurrents, and architectural analysis of the Tacaratu Formation, Northern Tucano Sub-basin, Brazil - Mateus do Nascimento Santana; Pedro Victor Oliveira Gomes; Felipe Torres Figueiredo (Journal of South American Earth Sciences, 2025)

What threats do Brazilian National parks face? - Alícia Helena Torres da Rocha; Jhonatan Guedes-Santos; Felipe Alexandre Santos Vieira; Ana Claudia Mendes Malhado; Richard J. Ladle; Jairo Lizandro Schmitt; Chiara Bragagnolo (Journal for Nature Conservation, 2025)

Causal interactions among phytoplankton and Pseudo-nitzschia species revealed by empirical dynamic modelling - Ishara Uhanie Perera; So Fujiyoshi; Daiki Kumakura; Carolina Medel; Kyoko Yarimizu; Oscar Espinoza-González; Leonardo Guzmán; Shinji Nakaoka; Felipe Tucca; Alexander Jaramillo-Torres; Yukako Tohsato; Jacquelinne J. Acuña; et al. (Marine Pollution Bulletin, 2025)

A novel bombesin-related peptide modulates glucose tolerance and insulin secretion in non-obese and hypothalamic-obese rats - Bruna Schumaker Siqueira; Marianela Andrea Díaz Urrutia; Vanessa Marieli Ceglarek; Daniel Carneiro Moreira; Felipe Torres Brasil Kuzniewski; José Roberto de Souza de Almeida Leite; Sabrina Grassiolli (Toxicon, 2025)

Growth-tolerance tradeoffs shape the survival outcomes and ecophysiological strategies of Atlantic Forest species in the rehabilitation of mining-impacted sites - Talita Raissa Silva Santos; Felipe Della Torre; Jessyca Adelle Silva Santos; Eduardo Gusmão Pereira; Queila Souza Garcia (Science of The Total Environment, 2025)

Pharmaceutical pollutants in water: Carbon nanotube–photocatalyst composites as a path forward - Karla J. Amaya-Galván; Karina J. Ramírez-Escárcega; Fausto L. Zaruma-Torres; Felipe de J. Silerio-Vázquez; José B. Proal-Nájera (Journal of Environmental Chemical Engineering, 2025)

Development and validation of a rapid method for the determination of oil and oleic acid content in peanut (Arachis hypogaea L.) using time domain nuclear magnetic resonance - Lucas J. Carvalho; Jacqueline Elis de Souza; Evelyn de F. Guimarães; Luiz Alberto Colnago; Daniel Martelozo Consalter; Silvia Paulo de Azevedo; Cristina Torres Consalter; Karla Borba; Rodrigo Garcia; Davi dos Santos Miquelin; Bruno Felipe Caravieri; Jair Heuert; et al. (Food Research International, 2025)

Palynological characterization of a diverse desertic ecosystem: the Peruvian Lomas - Axel Tejada-Fajardo; Juan-Felipe Montenegro; María-Isabel La Torre; Brenda Orosco; Diana Ochoa (Palynology, 2025)

Evaluation of the influence of the gas residence time and biomass concentration on methane bioconversion to ectoines in a novel Taylor flow bioreactor - Raquel Herrero-Lobo; Andrés Felipe Torres Franco; Raquel Lebrero; María del Rosario Rodero; Raúl Muñoz (Journal of Environmental Management, 2025)

Land-use change from native forest to avocado orchards: Effects on soil nutrient transformation and microbial communities - Brenda Baca-Patiño; Antonio González-Rodríguez; Felipe García-Oliva; Ariana García; Ingrid Lara-De La Cruz; Roberto Garibay-Orijel; Amisha Poret-Peterson; Yurixhi Maldonado-López; Pablo Cuevas-Reyes; Alberto Gómez-Tagle; Yunuen Tapia-Torres (Applied Soil Ecology, 2025)

Genetic parameters of meat quality, external morphology, and growth traits in Pacific white shrimp (Penaeus vannamei) from an Ecuadorian population - Marina Martínez Soler; Hyun Suk Shin; Álvaro Lorenzo-Felipe; María Jesús Zamorano Serrano; Rafael Ginés Ruiz; Laura Cristina Pachón Mesa; Darwin González; Jesús Fernández Martín; Juan Sebastián Ramírez Artiles; Adrián Peñate Sánchez; Javier Lorenzo Navarro; Ricardo Torres; et al. (Aquaculture, 2024)

Axial and transverse river deposits preserved in an Aptian rift basin, Northeastern Brazil: Implications for sandstone reservoir quality - Liliane Janikian; Renato Paes de Almeida; Felipe Torres Figueiredo; Bernardo Tavares Freitas; Natalia Naches Hilbert; Simone Campos Carrera; Marly Babinski; Maria Ramos-Clavijo; Cristiano Padalino Galeazzi; Gelson Luís Fambrini; Virgínio Henrique de Miranda Lopes Neumann (Marine and Petroleum Geology, 2024)

Influence of design and operational parameters of a Taylor flow reactor on the bioconversion of methane to ectoines - Raquel Herrero-Lobo; Andrés Felipe Torres Franco; Wendy Mylene Llamas-Ramos; Víctor Monsalvo; Patricia Zamora; Frank Rogalla; Raquel Lebrero; María del Rosario Rodero; Raúl Muñoz (Journal of Environmental Chemical Engineering, 2024)

Land use change and type of fertilization affect the stability and microbial activity, stoichiometry, and nutrient dynamics in agricultural and forest soils in Avándaro, México - José Alberto Morón-Cruz; Felipe García-Oliva; Yunuen Tapia-Torres (Applied Soil Ecology, 2024)

A machine learning approach to map the potential agroecological complexity in an indigenous community of Colombia - Cintya Katherine Ojeda Riaños; Carlos Alberto Torres; Juan Camilo Zapata Calero; Jhoana P. Romero-Leiton; Iván Felipe Benavides (Journal of Environmental Management, 2024)

Effect of ethanol extract from Enterolobium cyclocarpum fruit on Leghorn chickens exposed to Eimeria - Rosalinda Urtecho-Novelo; Ronald Santos-Ricalde; Luis Sarmiento-Franco; Juan Felipe Torres-Acosta; Rocío Borges-Árgaez (Tropical Animal Health and Production, 2024)

Measurement uncertainty for <711> Dissolution tests using Monte Carlo methods – Uncertainties arising from sampling and analytical steps - Maisa Torres Martins; Felipe Rebello Lourenço (Analytica Chimica Acta, 2024)

A two-stage deep learning strategy for weed identification in grassfields - Felipe Calderara-Cea; Miguel Torres-Torriti; Fernando Auat Cheein; José Delpiano (Computers and Electronics in Agriculture, 2024)

Optimization and discrete fractional-order PID controller applied to a pressure swing adsorption plant for the production and recovery of bioethanol - Jesús E. Valdez-Resendiz; Jesse Y. Rumbo-Morales; Felipe D.J. Sorcia-Vázquez; Gerardo Ortiz-Torres; J.F. Gómez-Aguilar; Carlos Alberto Torres Cantero; Moises Ramos-Martinez (Journal of Cleaner Production, 2024)

Calibration areas in ecological niche and species distribution modelling: Unravelling approaches and concepts - Octavio Rojas‐Soto; Juan S. Forero‐Rodríguez; Alejandra Galindo‐Cruz; Claudio Mota‐Vargas; Keisy D. Parra‐Henao; Alexander Peña‐Peniche; Javier Piña‐Torres; Karen Rojas‐Herrera; Juan D. Sánchez‐Rodríguez; Felipe A. Toro‐Cardona; Carlos D. Trinidad‐Domínguez (Journal of Biogeography, 2024)
Aim The calibration area (CA) corresponds to the geographic region used by different algorithms that estimate the species' environmental preferences and delimit its geographic distribution. This study intended to identify, test and compare current literature's most commonly employed approaches and methods for CA creation, highlighting the differences with the accessible area (M), a frequently misapplied concept. Location Global. Taxon Arthropods, amphibians, reptiles, birds and mammals. Methods We conducted a literature review and analysed 129 recent articles on species distribution that use correlative models to identify the methods used to establish the CA and their frequency. We also evaluated seven of the most widely used methods for 31 species from different taxa. Results We found that the most frequently used methods in literature corresponded to biogeographic entities (BE). Moreover, according to our evaluation, those methods that seek to establish the CA through the accessible area approach (including BE and ‘grinnell’) were the best evaluated. Finally, we highlight the advantages and disadvantages of the analysed methods in selecting CA. Main Conclusions Although we cannot fail to recognize the usefulness and validity of the different methods to establish CAs, we suggest calibrating ecological niche and species distribution models in light of explicit a priori hypotheses regarding the extent of accessible areas (M) as a delimitation of the CA, which theoretically includes the species' dispersal ability and its barriers. We recommend using the BE method, which is simple to establish and highly operational.

Bias-corrected high-resolution precipitation datasets assessment over a tropical mountainous region in Colombia: A case of study in Upper Cauca River Basin - Clara Marcela Romero-Hernández; Alvaro Avila-Diaz; Benjamin Quesada; Felipe Medeiros; Wilmar L. Cerón; Juan Guzman-Escalante; Camilo Ocampo-Marulanda; Roger Rodrigues Torres; Cristian Felipe Zuluaga (Journal of South American Earth Sciences, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

The in vitro rumen exsheathment test for studying the effect of plant extracts on the exsheathment of Haemonchus contortus infective larvae - Cindy Goretti Marin-Tun; Juan Felipe de Jesús Torres-Acosta; Concepción Manuela Capetillo-Leal; Carlos Alfredo Sandoval-Castro; Hervé Hoste; Rocío Borges-Argáez; María Gabriela Mancilla-Montelongo (Veterinary Parasitology, 2024)

Do invasive and native grasses in Brazilian Savanna differ in their photosynthetic performance under natural light radiation? - Áurea Rodrigues Cordeiro; Alexandre Aparecido Duarte; Felipe Della-Torre; Fernando Afonso Nonato França; Marcel Giovanni Costa França (Flora, 2024)

Pilot Monitoring of Lead in Umbilical Cord Blood of Newborns Associated With the Use of Glazed Ceramics from Guanajuato, Mexico - Jorge Alejandro Alegría-Torres; Diana Olivia Rocha-Amador; Rebeca Yazmín Pérez-Rodríguez; Valeria Monserrat Rodríguez-Felipe; Mayra Cauich-Díaz; Patricia Ponce-Noyola; Leticia Carrizales-Yáñez (Biological Trace Element Research, 2024)

Physico-chemical alteration of pyroxene in coastal environments: Empirical constraints from New Zealand and the Azores - Juan J. Kasper-Zubillaga; David M. Buchs; Duncan D. Muir; Lizeth Carlos-Delgado; Elsa Arellano-Torres; León Felipe Álvarez-Sánchez (Sedimentary Geology, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

Differentiating Bagasse and Straw as Feedstocks for Sugarcane Cellulosic Ethanol: Insights from Pilot-Scale Pretreatments - Viviane M. Nascimento; Simone C. Nakanishi; Carlos Alberto de Oliveira Filho; Absai da Conceição Gomes; Aline Machado de Castro; Ana Paula Rodrigues Torres; Christian Alejandro Queipo; Danuza Nogueira Moyses; Felipe de Oliveira Brito; Luiz Fernando Martins Bandeira; Carlos Driemeier (BioEnergy Research, 2024)

Adapting the in vitro rumen incubation method to evaluate the effect of a plant extract on the exsheathment inhibition of Haemonchus contortus infective larvae - Cindy Goretti Marin-Tun; María Gabriela Mancilla-Montelongo; Concepción Manuela Capetillo-Leal; Carlos Alfredo Sandoval-Castro; Hervé Hoste; Rocío Borges-Argáez; Juan Felipe de Jesús Torres-Acosta (Veterinary Parasitology, 2024)

Facies prediction in a mature oil field of Cretaceous age in the Calumbi Formation (Sergipe-Alagoas Basin, Brazil) by using an outcrop analogue approach - German Meneses Hernandez; Felipe Torres Figueiredo; Liliane Janikian; Mateus do Nascimento Santana; Pedro Victor Oliveira Gomes (Marine and Petroleum Geology, 2024)

Enhancing soil water retention and plant growth with thermal crosslinked silk sericin-based hydrogel - Natalia Jaramillo-Quiceno; Ana Sofía Duque Carmona; Juliana Serna Serna; Dora M. Carmona; Mabel Torres-Taborda; Gustavo Adolfo Hincapié-Llanos; Juan Felipe Santa Marín; Catalina Álvarez-López (Journal of Environmental Chemical Engineering, 2024)

Suitable areas for temperate fruit trees in a Brazilian hotspot area: Changes driven by new IPCC scenarios - Alysson Fernando Ribeiro; Fabrina Bolzan Martins; Diego Felipe dos Santos; Roger Rodrigues Torres; Flávia Fernanda Azevedo Fagundes (European Journal of Agronomy, 2024)

Pyrolysis: a promising technology for agricultural waste conversion into value-added products - Valdecir Ferrari; Mateus Torres Nazari; Nathalia Favarin da Silva; Larissa Crestani; Lucas Manique Raymundo; Guilherme Luiz Dotto; Jeferson Steffanello Piccin; Luis Felipe Silva Oliveira; Andrea Moura Bernardes (Environment, Development and Sustainability, 2024)

Controlled Elicitation and Greenhouse Acclimation Time Effects on Morphological and Biochemical Variables in Collections of Heliopsis longipes from Central México - Ixchel Parola-Contreras; Luis Felipe Guzman-Rodriguez; Erik Gustavo Tovar-Perez; Brenda Zulema Guerrero-Aguilar; Blanca Amalia Amaro-Gonzalez; Alejandra Rojas-Molina; Irineo Torres-Pacheco; Jose Luis Pons-Hernandez; Mario Martin Gonzalez-Chavira; Ramon Gerardo Guevara-Gonzalez (Journal of Plant Growth Regulation, 2024)

Genetic origin and morphometric traits of invasive African catfish (Clarias gariepinus) in a protected area in southeastern Brazil - Felipe Nóbrega; Michelle Torres Dumith; Fabiano Salgueiro; Alejandra F. G. N. Santos (Environmental Biology of Fishes, 2024)

The complexity of goats’ feeding behaviour: An overview of the research in the tropical low deciduous forest - Rafael Arturo Torres-Fajardo; Gabriel Ortíz-Domínguez; Pedro Geraldo González-Pech; Carlos Alfredo Sandoval-Castro; Juan Felipe de Jesús Torres-Acosta (Small Ruminant Research, 2024)

Chocolates, compounds and spreads: A review on the use of oleogels, hydrogels and hybrid gels to reduce saturated fat content - Rafael Fernandes Almeida; Lara Aguiar Borges; Thayná Torres da Silva; Nereide Serafim Timóteo dos Santos; Felipe Gianasi; Eduardo Augusto Caldas Batista; Priscilla Efraim (Food Research International, 2024)

Reviewing water types in Patagonia’s Atlantic seaboard - Américo Iadran Torres; Verena Agustina Campodonico; Mauricio Faleschini; Daniel Martínez; Luis Felipe Hax Niencheski; José Luis Esteves; Pedro José Depetris (Sustainable Water Resources Management, 2024)

Cytomolecular trends in Chamaecrista Moench (Caesalpinioideae, Leguminosae) diversification - Guilherme Tomaz Braz; Brena Van-Lume; Kátia Ferreira Marques de Resende; Felipe Pereira Cardoso; Ludmila Oliveira; Maria José Gomes de Andrade; Gustavo Souza; Giovana Augusta Torres (Genetica, 2024)

In vitro toxicity of fine and coarse particulate matter on the skin, ocular and lung microphysiological cell-culture systems - Dayan Yelena Guerra-Flórez; Laura Margarita Valencia-Osorio; Andrés Felipe Zapata-González; Mónica Lucía Álvarez-Láinez; Elizabeth Cadavid-Torres; Erick Alejandro Meneses-Ramírez; Viviana Torres-Osorio; Juan Sebastián Botero-Valencia; Andrés Pareja-López (Toxicology, 2023)

Business climate risk management: international perspectives and strategic determinants - Daniel Kouloukoui; Sonia Maria da Silva Gomes; Felipe Andrade Torres; Ednildo Andrade Torres (Environment, Development and Sustainability, 2023)

Biological traits as determinants in the macroecological patterns of distribution in loliginid squids - Christian M. Ibáñez; Amanda Luna; Carolina Márquez-Gajardo; Felipe I. Torres; Joao Bráullio L. Sales (Marine Biology, 2023)

Direct and indirect impacts of ocean acidification and warming on algae-herbivore interactions in intertidal habitats - Samanta Benítez; Jorge M. Navarro; Daniela Mardones; Paola A. Villanueva; Felipe Ramirez-Kushel; Rodrigo Torres; Nelson A. Lagos (Marine Pollution Bulletin, 2023)

Targeted treatment strategies for the control of gastrointestinal nematodes in a goat flock with anthelmintic resistant worm populations and poor nutrition - Gabriela Mancilla-Montelongo; Pedro Geraldo González-Pech; Dilcia Y. Miranda-Miranda; Gloria Sarahi Castañeda-Ramírez; Patricio Antonio Encalada-Aguilar; Alhely Can-Celis; Ivonne E. Galera-Chan; Gabriel Andrés Ortíz-Domínguez; Juan Felipe de Jesús Torres-Acosta (Small Ruminant Research, 2023)

Mapping crop producer perceptions: The role of global drivers on local agricultural land use in Brazil - Yue Dou; Ramon Felipe Bicudo da Silva; Mateus Batistella; Sara Torres; Emilio Moran; Jianguo Liu (Land Use Policy, 2023)

Perchlorate and chlorate assessment in drinking water in northern Chilean cities - Diana Muñoz-Arango; Felipe Torres-Rojas; Natalia Tapia; Marcela Vega; Cristobal Alvear; Gonzalo Pizarro; Pablo Pastén; Sandra Cortés; Alejandra S. Vega; Raúl Calderón; Robert Nerenberg; Ignacio T. Vargas (Environmental Research, 2023)

Synergistic effect of electrotrophic perchlorate reducing microorganisms and chemically modified electrodes for enhancing bioelectrochemical perchlorate removal - Felipe Torres-Rojas; Diana Muñoz; Camila Pía Canales; Samuel A. Hevia; Felipe Leyton; Nicolás Veloso; Mauricio Isaacs; Ignacio T. Vargas (Environmental Research, 2023)

Morphometrics of teratological specimens from two species of Plaxiphora (Mollusca, Polyplacophora) from the South Pacific Ocean - Felipe I. Torres; Óscar Gálvez-Herrera; Christian M. Ibáñez (Zoomorphology, 2023)

Late Cretaceous calcareous nannofossil assemblages from Colombia: Biostratigraphic contributions to northwestern South American Basins - Estefanía Angulo-Pardo; Felipe Vallejo-Hincapié; Rodrigo Do Monte Guerra; Andrés Pardo-Trujillo; Carlos A. Giraldo-Villegas; Jenny García González; Sebastian Hernández Duran; Sergio Herrera Quijano; Angelo Plata Torres; Raúl Trejos-Tamayo (Journal of South American Earth Sciences, 2023)

Effect of an organic acid blend in Nile tilapia growth performance, immunity, gut microbiota, and resistance to challenge against francisellosis - Vanessa Gomes da Silva; Leonardo Mantovani Favero; Raffaella Menegheti Mainardi; Natália Amoroso Ferrari; Roberta Torres Chideroli; Giovana Wingeter Di Santis; Felipe Pinheiro de Souza; Arthur Roberto da Costa; Daniela Dib Gonçalves; Waldo G. Nuez-Ortin; Maria Mercè Isern-Subich; Admilton Gonçalves de Oliveira-Junior; et al. (Research in Veterinary Science, 2023)

First molecular detection of Borrelia theileri subclinical infection in a cow from Brazil - Warley Vieira de Freitas Paula; Lucianne Cardoso Neves; Luiza Gabriella Ferreira de Paula; Maria Carolina de Azevedo Serpa; Fabricio Peixoto de Oliveira; Filipe Dantas‑Torres; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Felipe da Silva Krawczak (Veterinary Research Communications, 2023)

Use of δ15N and δ13C in reconstructing the ontogenetic feeding habits of silky shark (Carcharhinus falciformis): reassessing their trophic role in the Eastern Tropical Pacific Ocean - María Antonieta Galindo-Rosado; Felipe Galván-Magaña; Yassir Edén Torres-Rojas; Antonio Delgado-Huertas; Sergio Aguiñiga-García (Environmental Biology of Fishes, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Selecting tree species to restore forest under climate change conditions: Complementing species distribution models with field experimentation - Jesús Sandoval-Martínez; Ernesto I. Badano; Francisco A. Guerra-Coss; Jorge A. Flores Cano; Joel Flores; Sandra Milena Gelviz-Gelvez; Felipe Barragán-Torres (Journal of Environmental Management, 2023)

The FishPath approach for fisheries management in a data‐ and capacity‐limited world - Natalie A. Dowling; Jono R. Wilson; Jason M. Cope; Dawn T. Dougherty; Serena Lomonico; Carmen Revenga; Brian J. Snouffer; Natalio Godoy Salinas; Felipe Torres‐Cañete; Rowan C. Chick; Ashley M. Fowler; Ana M. Parma (Fish and Fisheries, 2023)
Successful fisheries management systems tend to be underpinned by harvest strategies, specifying formally agreed data collection systems, assessment approaches and management measures used to regulate fishing pressure. While harvest strategies can be effective even in data‐ and capacity‐limited (DCL) situations, their development remains challenging in such contexts. We present a process and decision‐support tool, FishPath, to guide the identification of suitable harvest strategy component options given often debilitating conditions: (i) resource limitations and lack of technical management capacity; (ii) ‘uniqueness’ of DCL fisheries; (iii) the concept of harvest strategies is unfamiliar to managers and scientists, and the universe of options is hard to navigate; and (iv) the lack of an effective participatory process to identify solutions tailored to local contexts. These conditions can lead to either management paralysis or generic solutions that may be poor fits to specific conditions. The FishPath Tool uses a diagnostic questionnaire that elicits the key characteristics and specific circumstances of a fishery. It compares these with the requirements of alternative options from an inventory of possible harvest strategy components, identifies where these requirements are met and provides customised, transparent guidance on the appropriateness of component options of a harvest strategy, specific to the fishery of interest and its governance context. The FishPath Process is a facilitated multi‐stakeholder, participatory engagement process aimed to set fisheries on the path to develop a harvest strategy. The FishPath Process and Tool combine to ensure a bottom‐up, documented, transparent, replicable and efficient process.

Pinnipeds carriers of pathogenic Leptospira: New data based on molecular characterization - Felipe D'Azeredo Torres; Ana Luiza dos Santos Baptista Borges; Cristiane Kolesnikovas; Camila Domit; Carla Beatriz Barbosa; Filipe Anibal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Research in Veterinary Science, 2023)

Ontogenetic shifts in feeding habits of orangemouth weakfish ( Cynoscion xanthulus ): From estuarine benthic feeder to marine nektivore top predator - Víctor M. Muro‐Torres; Felipe Amezcua; Lucinda Green; Jorge Payan; Eduardo F. Balart‐Páez; Felipe Amezcua‐Linares (Marine Ecology, 2023)
Orangemouth weakfish is a highly important commercial and game fish species in the Tropical Eastern Pacific. However, studies assessing changes in its trophic ecology relevant to size, habitat (estuarine or marine), sex, and season are non‐existent. We assessed its feeding habits and trophic position (TP) according to the aforementioned factors. Its dietary breadth was composed of 33 types of prey. The feeding habits and isotopic values (δ 15 N and δ 13 C) registered differences between sizes and habitat, indicating ontogenetic changes in habitat as well as TP, as small organisms (TP 3.1) inhabited the estuarine area, feeding on benthic and demersal organisms, whilst large individuals (TP 4.1) were found in the marine environment, preying on nektonic fauna. No differences were found according to sex or season. The isotopic niche showed that the different sizes of this species are generalist consumers with a clear separation between them and between habitats, as estuarine juvenile and preadult organisms have a larger isotopic niche than adult marine organisms, being an opportunist tertiary estuarine consumers during their early stages, and a top marine predator during the adult phase.

Early Eocene (Ypresian) palynology of marine sediments from the colombian Caribbean - Angelo Plata-Torres; Andrés Pardo-Trujillo; Felipe Vallejo-Hincapié; Raúl Trejos-Tamayo; José Abel Flores (Journal of South American Earth Sciences, 2023)

Effects of thermo-biological pretreatments on the combustion properties of wheat straw in a cascaded biorefinery concept - Patrick Beuel; Felipe Torres; Christiane Rieker; Jamile Bursche; Oliver Hensel (Fuel, 2023)

Eggshell microbiome as a potential microbial reservoir in a cavity nesting bird - Felipe Campos-Cerda; Roxana Torres; Liliana Nava; Cecilia Cuatianquiz-Lima; Yendi Navarro-Noya; Bibiana Montoya (Journal of Ornithology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Characterization and Identification of Probiotic Features in Lacticaseibacillus Paracasei Using a Comparative Genomic Analysis Approach - Alexis Torres-Miranda; Felipe Melis-Arcos; Daniel Garrido (Probiotics and Antimicrobial Proteins, 2022)

Comparing Latino Community Members’ and Clinical Staff’s Perspectives on Barriers and Facilitators to Colorectal Cancer Screening - Elizabeth N. Alpert; Tatiana Clark; Cristian Garcia-Alcaraz; Sumayah Nuhaily Eddington; Claudia Carrizosa; Jessica Haughton; Carolina Lopez de la Torre; Felipe Garcia-Bigley; Elva M. Arredondo; Christian Ramers; Jesse Nodora; Kristen J. Wells (Journal of Cancer Education, 2022)

Bio-directed Chemical Study of Pleurotus ostreatus Spent Substrate and Its Nematicidal Activity - Susan Yaracet Páez-León; Manasés González-Cortazar; José Ernesto Sánchez-Vázquez; Juan Felipe de Jesús Torres-Acosta; Maura Téllez-Téllez; Alejandro García-Flores; Gloria Sarahi Castañeda-Ramírez; Liliana Aguilar-Marcelino (Acta Parasitologica, 2022)

Enhancement of chlorhexidine activity against planktonic and biofilm forms of oral streptococci by two Croton spp. essential oils from the Caatinga biome - Brendda Miranda Vasconcelos; Antônio Mateus Gomes Pereira; Paulo Adenes Teixeira Coelho; Rafaela Mesquita Bastos Cavalcante; Daniela Santos Carneiro-Torres; Paulo Nogueira Bandeira; Felipe Ferreira da Silva; Tigressa Helena Soares Rodrigues; Geovany Amorim Gomes; Victor Alves Carneiro (Biofouling, 2022)

Pre and post stage of infection of Magnaporthe oryzae Oryza in wheat leaves with different resistance levels - Márcia Soares Chaves; Marciele Barbieri Antunes; Gerarda Beatriz Pinto da Silva; Felipe André Sganzerla Graichen; Gisele Abigail Montan Torres; José Antônio Martinelli (Brazilian Journal of Microbiology, 2022)

Cultivating vegetables in tailings from the Fundão dam collapse: metal accumulation and risks to food safety - Humberto Araújo Almeida; Felipe Della Torre; Queila Souza Garcia (Environmental Monitoring and Assessment, 2022)

Ticks on reptiles and amphibians in Central Amazonia, with notes on rickettsial infections - Filipe Dantas-Torres; Amanda Maria Picelli; Kamila Gaudêncio da Silva Sales; Lucas Christian de Sousa-Paula; Paulo Mejia; Igor Luis Kaefer; Lucio André Viana; Felipe Arley Costa Pessoa (Experimental and Applied Acarology, 2022)

In vitro Evaluation of the Nutraceutical Potential of Theobroma cacao pod Husk and Leaf Extracts for Small Ruminants - María Gabriela Mancilla-Montelongo; Gloria Sarahí Castañeda-Ramírez; Elodie Gaudin-Barbier; María Librada Canul-Velasco; José Israel Chan-Pérez; Álvaro De la Cruz-Cortazar; Celine Mathieu; Isabelle Fourquaux; Carlos Alfredo Sandoval-Castro; Hervé Hoste; Javier Ventura-Cordero; Pedro Geraldo González-Pech; et al. (Acta Parasitologica, 2021)

Characterization of Headache in COVID-19: a Retrospective Multicenter Study - Rafael César dos Anjos de Paula; Thaís de Maria Frota Vasconcelos; Francisco Bruno Santana da Costa; Lara Albuquerque de Brito; Danielle Mesquita Torres; Alissa Elen Formiga Moura; Danilo Nunes Oliveira; Guilherme Alves de Lima Henn; Pedro Gustavo Barros Rodrigues; Isabelle de Sousa Pereira; Ianna Lacerda Sampaio Braga; Felipe Araújo Rocha; et al. (Molecular Neurobiology, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Renewable energy planning policy for the reduction of poverty in Brazil: lessons from Juazeiro - Felipe Barroco Fontes Cunha; Maria Cândida Arrais de Miranda Mousinho; Luciana Carvalho; Fábio Fernandes; Celso Castro; Marcelo Santana Silva; Ednildo Andrade Torres (Environment, Development and Sustainability, 2021)

Seasonal dynamics of Amblyomma sculptum in two areas of the Cerrado biome midwestern Brazil, where human cases of rickettsiosis have been reported - Luiza Gabriella Ferreira de Paula; Viviane Zeringóta; Aparecida Lorrany Nunes Sampaio; Giovana Pereira Bezerra; Ana Laura Gonçalves Barreto; Andreza Alves dos Santos; Vanessa Carvalho Miranda; Warley Vieira de Freitas Paula; Lucianne Cardoso Neves; Mirna Vieira Secchis; Susy das Graças Alecrim Alves; Anaiá da Paixão Sevá; et al. (Experimental and Applied Acarology, 2021)

Salient brain entities labelled in P2rx7-EGFP reporter mouse embryos include the septum, roof plate glial specializations and circumventricular ependymal organs - Felipe Ortega; Rosa Gomez-Villafuertes; María Benito-León; Margaret Martínez de la Torre; Luis A. Olivos-Oré; Marina Arribas-Blazquez; María Victoria Gomez-Gaviro; Arturo Azcorra; Manuel Desco; Antonio R. Artalejo; Luis Puelles; María Teresa Miras-Portugal (Brain Structure and Function, 2021)
The purinergic system is one of the oldest cell-to-cell communication mechanisms and exhibits relevant functions in the regulation of the central nervous system (CNS) development. Amongst the components of the purinergic system, the ionotropic P2X7 receptor (P2X7R) stands out as a potential regulator of brain pathology and physiology. Thus, P2X7R is known to regulate crucial aspects of neuronal cell biology, including axonal elongation, path-finding, synapse formation and neuroprotection. Moreover, P2X7R modulates neuroinflammation and is posed as a therapeutic target in inflammatory, oncogenic and degenerative disorders. However, the lack of reliable technical and pharmacological approaches to detect this receptor represents a major hurdle in its study. Here, we took advantage of the P2rx7 -EGFP reporter mouse, which expresses enhanced green fluorescence protein (EGFP) immediately downstream of the P2rx7 proximal promoter, to conduct a detailed study of its distribution. We performed a comprehensive analysis of the pattern of P2X7R expression in the brain of E18.5 mouse embryos revealing interesting areas within the CNS. Particularly, strong labelling was found in the septum, as well as along the entire neural roof plate zone of the brain, except chorioidal roof areas, but including specialized circumventricular roof formations, such as the subfornical and subcommissural organs (SFO; SCO). Moreover, our results reveal what seems a novel circumventricular organ, named by us postarcuate organ (PArcO). Furthermore, this study sheds light on the ongoing debate regarding the specific presence of P2X7R in neurons and may be of interest for the elucidation of additional roles of P2X7R in the idiosyncratic histologic development of the CNS and related systemic functions.

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

Irradiance-driven 20-hydroxyecdysone production and morphophysiological changes in Pfaffia glomerata plants grown in vitro - Tatiane Dulcineia Silva; Diego Silva Batista; Kamila Motta Castro; Evandro Alexandre Fortini; Sérgio Heitor Sousa Felipe; Amanda Mendes Fernandes; Raysa Mayara Jesus Sousa; Kristhiano Chagas; José Victor Siqueira da Silva; Ludmila Nayara Freitas Correia; Gabriela Torres-Silva; Letícia Monteiro Farias; et al. (Protoplasma, 2021)

Positive interaction between shrubs and native orchids in a Mediterranean ecosystem - Cristian Atala; Mariela Baldelomar; Cristian Torres-Díaz; Guillermo Pereira; Felipe Cacciuttolo; Reinaldo Vargas; Marco A. Molina-Montenegro (Brazilian Journal of Botany, 2020)

AteqTERT expression and specific tissue activity in a 2-year-old complete plant in Agave tequilana in field conditions - Z. De la Torre Espinosa; Emmanuel Ávila De Dios; Felipe Sánchez Teyer; Enrique Castano (Brazilian Journal of Botany, 2020)

Climatic aspects and vertical structure circulation associated with the severe drought in Northeast Brazil (2012–2016) - Felipe Jeferson de Medeiros; Cristiano Prestrelo de Oliveira; Roger Rodrigues Torres (Climate Dynamics, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Deletion of the adenosine A2A receptor increases the survival rate in a mice model of polymicrobial sepsis - Miguel Meriño; Sebastián San Martín; Pedro Sandaña; Kurt Herlitz; Claudio Aguayo; Alejandro Godoy; Pablo Torres-Vergara; Marcelo Gonzalez; Felipe Troncoso; Jesenia Acurio; Carlos Escudero (Purinergic Signalling, 2020)

Assessing drought in the drylands of northeast Brazil under regional warming exceeding 4 °C - Jose A. Marengo; Ana Paula M. A. Cunha; Carlos A. Nobre; Germano G. Ribeiro Neto; Antonio R. Magalhaes; Roger R. Torres; Gilvan Sampaio; Felipe Alexandre; Lincoln M. Alves; Luz A. Cuartas; Karinne R. L. Deusdará; Regina C. S. Álvala (Natural Hazards, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Overview and future perspectives of nitrifying bacteria on biofilters for recirculating aquaculture systems - Pamela Ruiz; José Miguel Vidal; Daniela Sepúlveda; Claudia Torres; Gabriela Villouta; Carlos Carrasco; Felipe Aguilera; Nathaly Ruiz‐Tagle; Homero Urrutia (Reviews in Aquaculture, 2020)
Intensive fish culture is a practice in aquaculture systems; however, it can produce negative environmental impacts due to the accumulation of organic nitrogen from feeding procedures, but also from fish wasting products. Recirculating aquaculture systems have emerged as one strategy to reduce these impacts, maintaining a healthy environment for fish. These reduce toxicity level through nitrifying biofilters, which use a microbial consortium to convert ammonia into nitrate. The main component of bacterial consortium is comprised by aerobic ammonia‐oxidizing bacteria and aerobic nitrite‐oxidizing bacteria, which are part of the whole nitrification process. These nitrifying bacteria grow in suspension or in fixed form, the latter characterized by a biofilm formation where bacteria adhere to a physical substrate in a self‐produced polymer matrix. The biofilm formation requires tight communication among bacteria to regulate the transcriptional circuits underlying the production of chemical signal molecules (e.g. N‐acetyl‐homoserine lactones) that control biofilm formation. This coordination is known as quorum sensing and can be considered as a mechanism that contributes to the coupling and maintenance of nitrification rate among bacteria by regulating expression levels of relevant genes associated with nitrification process. Therefore, the control of this process is crucial in recirculating aquaculture systems and its incorrect manipulation can produce a detriment of water quality. We here present an overview of the nitrification process in recirculating aquaculture systems. Subsequently, we describe nitrifying biofilters and nitrifying bacteria. Finally, we discuss how quorum sensing controls the efficiency of nitrifying bacteria and potential applications of nitrifying biofilters in intensive aquaculture systems.

Chromium supplementation improves glucose metabolism and vaginal temperature regulation in Girolando cows under heat stress conditions in a climatic chamber - Lilian dos Santos Ribeiro; Felipe Zandonadi Brandão; Luciano de Rezende Carvalheira; Túlio José de Freitas Goes; Rodolpho de Almeida Torres Filho; Carolina Capobiango Romano Quintão; Maria de Fátima Ávila Pires; Luiz Sérgio de Almeida Camargo; Bruno Campos de Carvalho (Tropical Animal Health and Production, 2020)

Prevalence of PspA families and pilus islets among Streptococcus pneumoniae colonizing children before and after universal use of pneumococcal conjugate vaccines in Brazil - Patricia Alice Knupp-Pereira; Nayara Torres Cardoso Marques; Lúcia Martins Teixeira; Helvécio Cardoso Corrêa Póvoa; Felipe Piedade Gonçalves Neves (Brazilian Journal of Microbiology, 2020)

Microalgae harvesting by fungal-assisted bioflocculation - Mateus Torres Nazari; João Felipe Freitag; Vítor Augusto Farina Cavanhi; Luciane Maria Colla (Reviews in Environmental Science and Bio/Technology, 2020)

Active telomerase during leaf growth and increase of age in plants from Agave tequilana var. Azul - Zamaria Yoselin De la Torre-Espinosa; Felipe Barredo-Pool; Enrique Castaño de la Serna; Lorenzo Felipe Sánchez-Teyer (Physiology and Molecular Biology of Plants, 2020)

What happens to the ocean surface gravity waves when ENSO and MJO phases combine during the extended boreal winter? - Victor A. Godoi; Felipe M. de Andrade; Tom H. Durrant; Audalio R. Torres Júnior (Climate Dynamics, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Morphophysiological in vitro performance of Brazilian ginseng (Pfaffia glomerata (Spreng.) Pedersen) based on culture medium formulations - Tatiane Dulcineia Silva; Kristhiano Chagas; Diego Silva Batista; Sérgio Heitor Sousa Felipe; Eliza Louback; Lucas Torres Machado; Amanda Mendes Fernandes; Victor Hugo Teixeira Buttrós; Andréa Dias Koehler; Letícia Monteiro Farias; André Ferreira Santos; Priscila Oliveira Silva; et al. (In Vitro Cellular & Developmental Biology - Plant, 2019)

Nutritional and Sensory Quality of the Freshwater Prawn Macrobrachium rosenbergii and the Influence of Packaging Permeability on its Shelf Life - Julia Siqueira Simoes; Eliane Teixeira Mársico; César Aquiles Lázaro De La Torre; Sérgio Borges Mano; Robson Maia Franco; Luiz Felipe Lopes Dos Santos; Carlos Adam Conte-Junior (Journal of Aquatic Food Product Technology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Extrafloral nectaries of Cylindropuntia imbricata (Cactaceae) in the southern Chihuahuan Desert: anatomy and interaction with ants - Melissa Ávila-Argáez; Laura Yáñez-Espinosa; Ernesto Badano; Felipe Barragán-Torres; Joel Flores (Arthropod-Plant Interactions, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Assessment of acute toxicity and cytotoxicity of fluorescent markers produced by cardanol and glycerol, which are industrial waste, to different biological models - Bruno Ivo Pelizaro; Felipe Camargo Braga; Bruno do Amaral Crispim; Luiz Guilherme Maiolino Lacerda de Barros; Lucas Roberto Pessatto; Edwin José Torres Oliveira; Juliana Miron Vani; Antonio Pancrácio de Souza; Alexeia Barufatti Grisolia; Andréia Conceição Milan Brochado Antoniolli-Silva; Dênis Pires de Lima; Jeandre Augusto dos Santos Jaques; et al. (Environmental Science and Pollution Research, 2019)

Habitat suitability models to make conservation decisions based on areas of high species richness and endemism - Nathalie S. Hernández-Quiroz; Ernesto I. Badano; Felipe Barragán-Torres; Joel Flores; Carmelo Pinedo-Álvarez (Biodiversity and Conservation, 2018)

Phylogeography and species distribution modelling reveal the effects of the Pleistocene ice ages on an intertidal limpet from the south‐eastern Pacific - María Cecilia Pardo‐Gandarillas; Christian M. Ibáñez; Felipe I. Torres; Víctor Sanhueza; Alejandra Fabres; Joaquín Escobar‐Dodero; Fernando O. Mardones; Marco A. Méndez (Journal of Biogeography, 2018)
Aim The distribution and genetic composition of marine populations is the result of climatic and oceanographic factors as well as life history strategies. Studying species with wide distributions and high dispersal potential in sites that were differentially affected during the Pleistocene glaciations provides an opportunity to evaluate the genetic and distributional effect of glaciations on marine populations, such as the limpet Siphonaria lesonii . The aim of the present study is to evaluate the differential effects of glaciations on areas covered and not covered by ice sheets during the Pleistocene glaciations. Location Intertidal zone of the south‐eastern Pacific covering approximately 5,000 km of coastline of Peru and Chile. Methods We performed molecular analyses of mitochondrial and nuclear data jointly, as well as environmental niche modelling ( ENM ) of populations of the limpet Siphonaria lessonii . Using ENM , we modelled the potential distributional range of the species in the present and its distribution during the Last Glacial Maximum ( LGM ). Results Two lineages were found that were separated by a break at 41° S, corresponding to the biogeographical discontinuity previously reported for this region. Both of these lineages experienced genetic and demographical fluctuations that match the Pleistocene glaciations; however, the variability was more intense in the southern lineage. Phylogeography and ENM yielded complementary results for the southern lineage, which experienced loss of genetic diversity and habitat during the LGM , whereas the northern lineage evidenced loss of genetic diversity without distributional changes. Main conclusions The phylogeographical and ENM approaches suggest a historical scenario involving demographic and distributional contractions of S. lessonii surviving in glacial refugia in the southern portion of the south‐eastern Pacific. This study is the first to include both phylogeographical and ENM analyses of marine species from the Southern Hemisphere.

Nucleotide Diversity of the Coding and Promoter Regions of DREB1D, a Candidate Gene for Drought Tolerance in Coffea Species - Gabriel Sergio Costa Alves; Luana Ferreira Torres; Sinara Oliveira de Aquino; Tharyn Reichel; Luciana Perreira Freire; Natalia Gomes Vieira; Felipe Vinecky; Dominique This; David Pot; Hervé Etienne; Luciano Vilela Paiva; Pierre Marraccini; et al. (Tropical Plant Biology, 2018)

Light quality in plant tissue culture: does it matter? - Diego Silva Batista; Sergio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Kamila Motta de Castro; Talita Cristina Mamedes-Rodrigues; Natane Amaral Miranda; Anyela Marcela Ríos-Ríos; Daniele Vidal Faria; Evandro Alexandre Fortini; Kristhiano Chagas; Gabriela Torres-Silva; Aloisio Xavier; et al. (In Vitro Cellular & Developmental Biology - Plant, 2018)

Effects of polyphenol removal methods on the in vitro exsheathment inhibitory activity of Lysiloma latisiliquum extracts against Haemonchus contortus larvae - Gloria Ivonne Hernández-Bolio; Karlina García-Sosa; Fabiola Escalante-Erosa; Gloria Sarahi Castañeda-Ramírez; Enrique Sauri-Duch; Juan Felipe de Jesús Torres-Acosta; Luis Manuel Peña-Rodríguez (Natural Product Research, 2018)

Differential sensitivity of total and active soil microbial communities to drought and forest management - Felipe Bastida; Irene F. Torres; Manuela Andrés‐Abellán; Petr Baldrian; Rubén López‐Mondéjar; Tomáš Větrovský; Hans H. Richnow; Robert Starke; Sara Ondoño; Carlos García; Francisco R. López‐Serrano; Nico Jehmlich (Global Change Biology, 2017)
Climate change will affect semiarid ecosystems through severe droughts that increase the competition for resources in plant and microbial communities. In these habitats, adaptations to climate change may consist of thinning—that reduces competition for resources through a decrease in tree density and the promotion of plant survival. We deciphered the functional and phylogenetic responses of the microbial community to 60 years of drought induced by rainfall exclusion and how forest management affects its resistance to drought, in a semiarid forest ecosystem dominated by Pinus halepensis Mill. A multi OMIC approach was applied to reveal novel, community‐based strategies in the face of climate change. The diversity and the composition of the total and active soil microbiome were evaluated by 16S rRNA gene (bacteria) and ITS (fungal) sequencing, and by metaproteomics. The microbial biomass was analyzed by phospholipid fatty acids ( PLFA s), and the microbially mediated ecosystem multifunctionality was studied by the integration of soil enzyme activities related to the cycles of C, N, and P. The microbial biomass and ecosystem multifunctionality decreased in drought‐plots, as a consequence of the lower soil moisture and poorer plant development, but this decrease was more notable in unthinned plots. The structure and diversity of the total bacterial community was unaffected by drought at phylum and order level, but did so at genus level, and was influenced by seasonality. However, the total fungal community and the active microbial community were more sensitive to drought and were related to ecosystem multifunctionality. Thinning in plots without drought increased the active diversity while the total diversity was not affected. Thinning promoted the resistance of ecosystem multifunctionality to drought through changes in the active microbial community. The integration of total and active microbiome analyses avoids misinterpretations of the links between the soil microbial community and climate change.

Early metal pollution in southwestern Europe: the former littoral lagoon of El Almarjal (Cartagena mining district, S.E. Spain).A sedimentary archive more than 8000 years old - José-Ignacio Manteca; Milagros Ros-Sala; Sebastián Ramallo-Asensio; Francisca Navarro-Hervás; Tomás Rodríguez-Estrella; Felipe Cerezo-Andreo; José-Eugenio Ortiz-Menéndez; Trinidad de-Torres; Miguel Martínez-Andreu (Environmental Science and Pollution Research, 2017)

Plant extracts as phytogenic additives considering intake, digestibility, and feeding behavior of sheep - Camila Sousa da Silva; Evaristo Jorge Oliveira de Souza; Gerfesson Felipe Cavalcanti Pereira; Edwilka Oliveira Cavalcante; Ewerton Ivo Martins de Lima; Thaysa Rodrigues Torres; José Ricardo Coelho da Silva; Daniel Cézar da Silva (Tropical Animal Health and Production, 2017)

Evaluation of different models to segregate Pelibuey and Katahdin ewes into resistant or susceptible to gastrointestinal nematodes - Jovanny Gaspar Palomo-Couoh; Armando Jacinto Aguilar-Caballero; Juan Felipe de Jesús Torres-Acosta; Juan Gabriel Magaña-Monforte (Tropical Animal Health and Production, 2016)

Total replacement of corn by mesquite pod meal considering nutritional value, performance, feeding behavior, nitrogen balance, and microbial protein synthesis of Holstein-Zebu crossbred dairy steers - Gláucia Sabrine de Oliveira Moraes; Evaristo Jorge Oliveira de Souza; Antonia Sherlânea Chaves Véras; Marina de Paula Almeida; Márcio Vieira da Cunha; Thaysa Rodrigues Torres; Camila Sousa da Silva; Gerfesson Felipe Cavalcanti Pereira (Tropical Animal Health and Production, 2016)

Evaluation of Learning in Oncology of Undergraduate Nursing with the Use of Concept Mapping - Mariane Trevisani; Cibelli Rizzo Cohrs; Mariângela Abate de Lara Soares; José Marcio Duarte; Felipe Mancini; Ivan Torres Pisa; Edvane Birelo Lopes De Domenico (Journal of Cancer Education, 2016)

The active microbial diversity drives ecosystem multifunctionality and is physiologically related to carbon availability in Mediterranean semi‐arid soils - Felipe Bastida; Irene F. Torres; José L. Moreno; Petr Baldrian; Sara Ondoño; Antonio Ruiz‐Navarro; Teresa Hernández; Hans H. Richnow; Robert Starke; Carlos García; Nico Jehmlich (Molecular Ecology, 2016)
Biogeochemical processes and ecosystemic functions are mostly driven by soil microbial communities. However, most methods focus on evaluating the total microbial community and fail to discriminate its active fraction which is linked to soil functionality. Precisely, the activity of the microbial community is strongly limited by the availability of organic carbon (C) in soils under arid and semi‐arid climate. Here, we provide a complementary genomic and metaproteomic approach to investigate the relationships between the diversity of the total community, the active diversity and ecosystem functionality across a dissolved organic carbon ( DOC ) gradient in southeast Spain. DOC correlated with the ecosystem multifunctionality index composed by soil respiration, enzyme activities (urease, alkaline phosphatase and β‐glucosidase) and microbial biomass (phospholipid fatty acids, PLFA ). This study highlights that the active diversity (determined by metaprotoemics) but not the diversity of the whole microbial community (evaluated by amplicon gene sequencing) is related to the availability of organic C and it is also connected to the ecosystem multifunctionality index. We reveal that DOC shapes the activities of bacterial and fungal populations in Mediterranean semi‐arid soils and determines the compartmentalization of functional niches. For instance, Rhizobales thrived at high‐ DOC sites probably fuelled by metabolism of one‐C compounds. Moreover, the analysis of proteins involved in the transport and metabolism of carbohydrates revealed that Ascomycota and Basidiomycota occupied different nutritional niches. The functional mechanisms for niche specialization were not constant across the DOC gradient.

Time-Based Network Analysis Before and After the $$M_w$$ M w 8.3 Illapel Earthquake 2015 Chile - Denisse Pastén; Felipe Torres; Benjamín Toledo; Víctor Muñoz; José Rogan; Juan Alejandro Valdivia (Pure and Applied Geophysics, 2016)

Soluble hydrocarbons uptake by porous carbonaceous adsorbents at different water ionic strength and temperature: something to consider in oil spills - Carlos E. Flores-Chaparro; Luis Felipe Chazaro Ruiz; Ma. Catalina Alfaro-De la Torre; Jose Rene Rangel-Mendez (Environmental Science and Pollution Research, 2016)

Cavβ2 transcription start site variants modulate calcium handling in newborn rat cardiomyocytes - Cristian Moreno; Tamara Hermosilla; Danna Morales; Matías Encina; Leandro Torres-Díaz; Pablo Díaz; Daniela Sarmiento; Felipe Simon; Diego Varela (Pflügers Archiv - European Journal of Physiology, 2015)

In and out of refugia: historical patterns of diversity and demography in the North American Caesar's mushroom species complex - Santiago Sánchez‐Ramírez; Rodham E. Tulloss; Laura Guzmán‐Dávalos; Joaquín Cifuentes‐Blanco; Ricardo Valenzuela; Arturo Estrada‐Torres; Felipe Ruán‐Soto; Raúl Díaz‐Moreno; Nallely Hernández‐Rico; Mariano Torres‐Gómez; Hugo León; Jean‐Marc Moncalvo (Molecular Ecology, 2015)
Some of the effects of past climate dynamics on plant and animal diversity make‐up have been relatively well studied, but to less extent in fungi. Pleistocene refugia are thought to harbour high biological diversity (i.e. phylogenetic lineages and genetic diversity), mainly as a product of increased reproductive isolation and allele conservation. In addition, high extinction rates and genetic erosion are expected in previously glaciated regions. Some of the consequences of past climate dynamics might involve changes in range and population size that can result in divergence and incipient or cryptic speciation. Many of these dynamic processes and patterns can be inferred through phylogenetic and coalescent methods. In this study, we first delimit species within a group of closely related edible ectomycorrhizal Amanita from North America (the American Caesar's mushrooms species complex) using multilocus coalescent‐based approaches; and then address questions related to effects of Pleistocene climate change on the diversity and genetics of the group. Our study includes extensive geographical sampling throughout the distribution range, and DNA sequences from three nuclear protein‐coding genes. Results reveal cryptic diversity and high speciation rates in refugia. Population sizes and expansions seem to be larger at midrange latitudes (Mexican highlands and SE USA ). Range shifts are proportional to population size expansions, which were overall more common during the Pleistocene. This study documents responses to past climate change in fungi and also highlights the applicability of the multispecies coalescent in comparative phylogeographical analyses and diversity assessments that include ancestral species.

Mercury and Selenium in Muscle and Target Organs of Scalloped Hammerhead Sharks Sphyrna lewini of the SE Gulf of California: Dietary Intake, Molar Ratios, Loads, and Human Health Risks - Magdalena E. Bergés-Tiznado; Fernando Márquez-Farías; Raúl E. Lara-Mendoza; Yassir E. Torres-Rojas; Felipe Galván-Magaña; Humberto Bojórquez-Leyva; Federico Páez-Osuna (Archives of Environmental Contamination and Toxicology, 2015)

Stable isotope analysis versus TROPH: a comparison of methods for estimating fish trophic positions in a subtropical estuarine system - Felipe Amezcua; Víctor Muro-Torres; Martín F. Soto-Jiménez (Aquatic Ecology, 2015)

Exogenously induced brain activation regulates neuronal activity by top-down modulation: conceptualized model for electrical brain stimulation - Lauren Naomi Spezia Adachi; Alexandre Silva Quevedo; Andressa de Souza; Vanessa Leal Scarabelot; Joanna Ripoll Rozisky; Carla de Oliveira; Paulo Ricardo Marques Filho; Liciane Fernandes Medeiros; Felipe Fregni; Wolnei Caumo; Iraci L. S. Torres (Experimental Brain Research, 2015)

Effects of roads on insects: a review - Pilar Tamayo Muñoz; Felipe Pascual Torres; Adela González Megías (Biodiversity and Conservation, 2015)

Characterization of methicillin-resistant coagulase-negative staphylococci in milk from cows with mastitis in Brazil - Nathalia C. C. Silva; Felipe F. Guimarães; Marcela de P. Manzi; Elena Gómez-Sanz; Paula Gómez; Joao P. Araújo-Júnior; Helio Langoni; Vera L. M. Rall; Carmen Torres (Antonie van Leeuwenhoek, 2014)

Feeding grounds of juvenile scalloped hammerhead sharks (Sphyrna lewini) in the south-eastern Gulf of California - Yassir Edén Torres Rojas; Federico Páez Osuna; Agustín Hernández Herrera; Felipe Galván Magaña; Sergio Aguiñiga García; Héctor Villalobos Ortíz; Laura Sampson (Hydrobiologia, 2014)

Transferability of molecular markers from major legumes to Lathyrus spp. for their application in mapping and diversity studies - Nuno Felipe Almeida; Susana Trindade Leitão; Constantino Caminero; Ana Maria Torres; Diego Rubiales; Maria Carlota Vaz Patto (Molecular Biology Reports, 2014)

The importance for food security of maintaining rust resistance in wheat - Márcia Soares Chaves; José Antônio Martinelli; Caroline Wesp-Guterres; Felipe André Sganzerla Graichen; Sandra Patussi Brammer; Sandra Mansur Scagliusi; Paulo Roberto da Silva; Paula Wiethölter; Gisele Abigail Montan Torres; Elene Yamazaki Lau; Luciano Consoli; Ana Lúcia Soares Chaves (Food Security, 2013)

Feeding ecology and trophic level of the banded guitarfish, Zapteryx exasperata, inferred from stable isotopes and stomach contents analysis - María-del-Pilar Blanco-Parra; Felipe Galván-Magaña; J. Fernando Márquez-Farías; Carlos Alberto Niño-Torres (Environmental Biology of Fishes, 2012)

After-effects of consecutive sessions of transcranial direct current stimulation (tDCS) in a rat model of chronic inflammation - Gabriela Laste; Wolnei Caumo; Lauren Naomi Spezia Adachi; Joanna Ripoll Rozisky; Isabel Cristina de Macedo; Paulo Ricardo Marques Filho; Wania Aparecida Partata; Felipe Fregni; Iraci L. S. Torres (Experimental Brain Research, 2012)

Indirect somatic embryogenesis and morphohistological analysis in Capsicum chinense - Laura Y. Solís-Ramos; Sara Nahuath-Dzib; Antonio Andrade-Torres; Felipe Barredo-Pool; Tomas González-Estrada; Enrique Castaño de la Serna (Biologia, 2010)

Stomach content analysis of juvenile, scalloped hammerhead shark Sphyrna lewini captured off the coast of Mazatlán, Mexico - Yassir Edén Torres-Rojas; Agustín Hernández-Herrera; Felipe Galván-Magaña; Vanessa Guadalupe Alatorre-Ramírez (Aquatic Ecology, 2010)

ISOTOPIC ANALYSIS OF δ 13 C, δ 15 N, AND δ 34 S “A FEEDING TALE” IN TEETH OF THE LONGBEAKED COMMON DOLPHIN, DELPHINUS CAPENSIS - Carlos Alberto Niño‐Torres; Juan Pablo Gallo‐Reynoso; Felipe Galván‐Magaña; Elva Escobar‐Briones; Stephen A. Macko (Marine Mammal Science, 2006)
Stable isotopic analyses of carbon, nitrogen, and sulfur were performed on teeth of different ages and sexes of the longbeaked common dolphin, Delphinus capensis, from the Gulf of California. Similarities in diet are suggested between the sexes, with no significant differences in isotopic compositions being observed. Differences in the δ 13 C, δ 15 N, and δ 34 S signatures were found among the age groups (nursing calf, juvenile, subadult, and adult). These data suggest that this species is generally a coastal feeder, and that it changes its feeding habits with increasing age, drawing more nutrition from higher trophic level organisms later in life.